2007
DOI: 10.1164/rccm.200612-1771oc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia Induces Atherosclerosis

Abstract: Rationale: Obstructive sleep apnea, a condition leading to chronic intermittent hypoxia (CIH), is associated with hyperlipidemia, atherosclerosis, and a high cardiovascular risk. A causal link between obstructive sleep apnea and atherosclerosis has not been established. Objectives: The objective of the present study was to examine whether CIH may induce atherosclerosis in C57BL/6J mice. Methods: Forty male C57BL/6J mice, 8 weeks of age, were fed either a high-cholesterol diet or a regular chow diet and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
247
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(272 citation statements)
references
References 55 publications
17
247
1
7
Order By: Relevance
“…After the first acute myocardial infarction, 65.7% of patients had an apnea-hypopnea index ≥ 15/h 35 . In other studies, the prevalence of OSA in patients with artery heart disease ranged from 43 to 66.4% 36,37,38,39 . The prevalence of a high risk of coronary artery disease associated with OSA in our survey was within these estimates.…”
Section: Discussionmentioning
confidence: 75%
“…After the first acute myocardial infarction, 65.7% of patients had an apnea-hypopnea index ≥ 15/h 35 . In other studies, the prevalence of OSA in patients with artery heart disease ranged from 43 to 66.4% 36,37,38,39 . The prevalence of a high risk of coronary artery disease associated with OSA in our survey was within these estimates.…”
Section: Discussionmentioning
confidence: 75%
“…7 Chronic intermittent hypoxia causes dyslipidaemia and initiates the development of atherosclerosis, both of which contribute to arterial stiffness. 24 Decreasing nocturnal apnea-hypopnea by CPAP treatment may protect OSA patients from the progression of arterial stiffness, as well as decreasing blood pressure in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress would result in the activation of inflammatory pathways [38,39], such as those mediated by nuclear factor-kB, tumour necrosis factor-a, interleukin (IL)-6 and IL-8, all parameters that are found to be elevated in OSAS patients and modified by therapy [21,25]. Studies in humans [40] have confirmed the key role of chronic intermittent hypoxia, more than that of the AHI, in the development of atherosclerosis in SDB and on partial reversal by efficacious therapy [41]. Therefore, atherosclerotic lesions and inflammatory processes, induced by intermittent hypoxia, contribute to long-term increased cardiovascular morbidity and mortality described in patients with SDB [42,43].…”
Section: Discussionmentioning
confidence: 99%